Improving the Fertigation of Soilless Urban Vertical Agriculture Through the Combination of Struvite and Rhizobia Inoculation in Phaseolus vulgaris - Arcas-Pilz, Verónica; Parada, Felipe; Villalba, Gara; Rufí-Salis, Martí; Rosell-Melé, Antoni; Gabarrell Durany, Xavier (Frontiers in Plant Science, 2021)
Soilless crop production is a viable way to promote vertical agriculture in urban areas but relies extensively on the use of mineral fertilizer. Thus, the benefits of fresher, local food and avoiding the transportation and packaging that are associated with food imports could be counteracted by an increase in nutrient-rich wastewater, which could contribute to freshwater and marine eutrophication. The present study aimed to explore the use of mineral fertilizer substitutes in soilless agriculture. Phaseolus vulgaris (common bean) was fertilized with a combination of slow-releasing fertilizer struvite (a source of N, P, and Mg), which is a byproduct of wastewater treatment plants, and inoculation with Rhizobium (a N2-fixing soil bacteria). The experiment included three bean production lines: A) 2 g/plant of struvite and rhizobial inoculation; B) 5 g/plant of struvite and rhizobial inoculation, both irrigated with a Mg-, P- and N-free nutrient solution; and C) a control treatment that consisted of irrigation with a full nutrient solution and no inoculation. Plant growth, development, yields and nutrient contents were determined at 35, 62 and 84 days after transplanting, as well as biological N2 fixation that was determined using the 15N natural abundance method. Treatments A and B resulted in lower total yields per plant than the control C treatment (e.g., 59.35± 26.4 g plant-1 for A, 74.2±23.0 g plant-1 for B and 147.71± 45.3 g plant-1 for C). For A and B, the nodulation and N2 fixation capacities appeared to increase with the amount of initially available struvite, but over time, deficient levels of Mg were reached as well as nearly deficient levels of P, which could explain the lower yields. Nevertheless, we conclude that the combination of struvite and N2-fixing bacteria covered the N needs of plants throughout the growth cycle. However, further studies are needed to determine the optimal struvite quantities for vertical agriculture systems that can meet the P and Mg requirements throughout the lifetime of the plants.